(Re)Organizing legitimacy theory. (20th June 2022) - Hamm, Joseph A.; Wolfe, Scott E.; Cavanagh, Caitlin; Lee, Sung
Abstract : Purpose: Despite a common conceptual root, research applying legitimacy theory addresses any number of more or less distinct behaviours, attitudes, and processes. Although this variety in approaches has complicated theoretical development, we argue that it is critical to addressing the breadth of the construct. To address this state of affairs, we offer the Concentric Diagram of Legitimacy as an organizing tool for the literature. The diagram roots itself in the dialogue of legitimacy, and argues that legitimacy theory is fundamentally comprised of five key theoretical propositions. Proposition 1 addresses the link between authority and acquiescence directly while the remaining propositions link organizational support (Proposition 2) and public approval (Proposition 3) with authority, and interactions (Proposition 4) and the social context (Proposition 5) with acquiescence.